2022
DOI: 10.5694/mja2.51619
|View full text |Cite
|
Sign up to set email alerts
|

The short term safety ofCOVID‐19 vaccines in Australia:AusVaxSafetyactive surveillance, February – August 2021

Abstract: Objective To assess the short term safety of the COVID‐19 vaccines Comirnaty (Pfizer–BioNTech BNT162b2) and Vaxzevria (AstraZeneca ChAdOx1) in Australia. Design Prospective observational cohort study; online surveys by AusVaxSafety, a national active vaccine safety surveillance system, three and eight days after vaccination. Setting, participants People aged 16 years or more who received COVID‐19 vaccines at sentinel vaccination hubs, general practices, or Aboriginal Community Controlled Health Organisation cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
2
10
0
1
Order By: Relevance
“…Atualmente, os centros de vacinação COVID-19 encontram-se sob alçada da medicina geral e familiar e o centro de saúde é a principal porta de entrada do utente nos serviços de saúde, pelo que importa relembrar a rabdomiólise como um possível efeito adverso das vacinas contra a COVID-19. Efetivamente, podem surgir mialgias de ligeira intensidade e rápida resolução até três dias a seguir à vacinação [10][11] e o médico de família deverá estar apto a identificar a sintomatologia, que não se enquadra no padrão expectável, para agir em conformidade.…”
Section: Comentáriounclassified
“…Atualmente, os centros de vacinação COVID-19 encontram-se sob alçada da medicina geral e familiar e o centro de saúde é a principal porta de entrada do utente nos serviços de saúde, pelo que importa relembrar a rabdomiólise como um possível efeito adverso das vacinas contra a COVID-19. Efetivamente, podem surgir mialgias de ligeira intensidade e rápida resolução até três dias a seguir à vacinação [10][11] e o médico de família deverá estar apto a identificar a sintomatologia, que não se enquadra no padrão expectável, para agir em conformidade.…”
Section: Comentáriounclassified
“…In the largest published post‐marketing analysis of the safety of the Comirnaty and Vaxzevria vaccines, Lucy Deng and colleagues 13 analysed data from online AusVaxSafety surveys of more than three million people aged 16 years or more. The authors found that adverse events were more frequently reported by people with underlying medical conditions, including a history of anaphylaxis.…”
Section: Our Best Original Research Articles In 2022mentioning
confidence: 99%
“…Australian data contribute to the international body of evidence regarding vaccine safety, adds information on specific groups in our country (including Indigenous Australians), and permits comparisons between the vaccines used locally. Both the rapid establishment of reactogenicity profiles and the awareness that AEFI are actively being sought facilitates public confidence in vaccines 10,13 …”
mentioning
confidence: 99%
“…In the study reported in this issue of the MJA , 10 Deng and colleagues analysed AusVaxSafety data for more than three million vaccination episodes. While the response rate to the survey was relatively high (63%), the authors may have overestimated the frequency of adverse events because non‐responders are less likely to have experienced significant reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation